PERAN KOMISI PERLINDUNGAN ANAK INDONESIA TERHADAP KORBAN PENCABULAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 85/PUU-XVII/2019 - Jidny Izham Al Fasha; Moch. Daffa Syahrizal (Paulus Law Journal, 2022)
Because the realization of the functions and tasks of the Indonesian Child Protection Commission is aimed at child victims of sexual abuse crimes throughout Indonesia, efforts to optimize the functions and tasks are very necessary so that the limited reach does not interfere with its realization. This research is intended to provide an overview of the realization and optimization of the functions and tasks of the Indonesian Child Protection Commission. The research method used in this paper is a normative juridical approach and an analytical method using a qualitative juridical approach. Based on the results of the research, the Indonesian Child Protection Commission realizes its functions and tasks by prioritizing its suitability for a child molestation case as an ordinary offense that needs to be processed properly under the supervision of the Indonesian Child Protection Commission, which is oriented towards the protection of child victims. Regarding optimization, the Indonesian Child Protection Commission needs to collaborate with Non-Governmental Organizations as part of civil society and also synergize with the Regional Government considering that the Constitutional Court has rejected the application for a judicial review of the child protection law regarding the Regional Child Protection Commission